2021
DOI: 10.1519/ssc.0000000000000688
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strength Training on Blood Pressure and Heart Rate Variability—A Systematic Review

Abstract: Strength training (ST) has been studied for acute and chronic effects on blood pressure (BP) and heart rate variability (HRV). These effects have never been reviewed collectively concerning the variables that comprise a ST program. Therefore, this review aims to examine the manipulation of ST variables (i.e., load intensity, number of sets and repetitions, exercise order, and rest interval length) on BP and HRV after a session and a long-term program. The BP reduced significantly after an ST session independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 75 publications
(203 reference statements)
0
14
0
Order By: Relevance
“…We identified only four systematic reviews without metaanalyses elucidating mechanisms of PEH based on exercise modality: one focusing on aerobic [31], another on aerobic/ resistance [33], and two specifically on resistance exercisesisometric [50] and dynamic [51]. The primary trials within these systematic reviews examined young or older adults with normal/elevated [31,51] or elevated BP [33], or middleaged and older adults with elevated BP [50].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified only four systematic reviews without metaanalyses elucidating mechanisms of PEH based on exercise modality: one focusing on aerobic [31], another on aerobic/ resistance [33], and two specifically on resistance exercisesisometric [50] and dynamic [51]. The primary trials within these systematic reviews examined young or older adults with normal/elevated [31,51] or elevated BP [33], or middleaged and older adults with elevated BP [50].…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…We identified only four systematic reviews without metaanalyses elucidating mechanisms of PEH based on exercise modality: one focusing on aerobic [31], another on aerobic/ resistance [33], and two specifically on resistance exercisesisometric [50] and dynamic [51]. The primary trials within these systematic reviews examined young or older adults with normal/elevated [31,51] or elevated BP [33], or middleaged and older adults with elevated BP [50]. Anunciac ¸ão and Polito [33] compared aerobic and resistance exercise, highlighting that acute aerobic exercise led to BP reductions associated with decreased SVR, while BP reductions from resistance exercise were linked to reduced Q. Brito et al [31] explored moderators of PEH, concluding that reduced Q played a greater role in PEH compared with reductions in SVR in older vs. young, overweight vs. normal weight, and elevated vs. normal BP samples.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…In their systematic review, Corso et al 7 identified only three chronic resistance training studies, of which only one study demonstrated a significant reduction in SBP. 7 All the rest interval groups in this study experienced a significant reduction in their SBP after 8 weeks of resistance training.…”
Section: Discussionmentioning
confidence: 99%
“…In their systematic review, Corso et al 7 identified only three chronic resistance training studies, of which only one study demonstrated a significant reduction in SBP. 7 All the rest interval groups in this study experienced a significant reduction in their SBP after 8 weeks of resistance training. Limitations of this study include self-reporting of blood pressure and exercise data, nutritional factors, and anxiety levels experienced by the participants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation